PENGARUH PENGGUNAAN METODE RESITASI BERBANTUAN MEDIA BULLETIN BOARD DISPLAY TERHADAP HASIL BELAJAR SISWA MIN 2 BENER MERIAH - Rahmah Rahmah; Daniah Daniah; Arusman Arusman (PIONIR: JURNAL PENDIDIKAN, 2022)
The learning process at MIN 2 Bener Meriah already uses learning methods, but it is not optimal and not fully in accordance with the material being taught, the lack of media use, learning is student centered learning so that it causes students difficulty in understanding the material being taught. The purpose of this study was to determine student learning outcomes through the recitation method assisted by the bulletin board display media and student responses to the methods and media used. The data collection method used quasi-experimental with nonequivalent pre-test post-test control group design. Sampling was done by purposive sampling, namely the experimental class as many as 30 students and the control class as many as 30 students. The research instrument is a test in the form of multiple choice and a questionnaire. Analysis of learning outcomes using t-test and student responses using the percentage of respondents formula. Based on the results of data analysis, it was obtained (a) the results of the t test, namely tcount of 6.27 and ttable of 1.672 (tcount> ttable) so that Ha was accepted and Ho was rejected and the regression test was Y = 71.50 + 0.09X, (b) response students to the recitation method assisted by bulletin board display media with a percentage of 69.3% agree. Based on the results of this study, it can be concluded that there is an effect of using the recitation method with the help of bulletin board display media on student learning outcomes and students are happy and interested in the learning process using the bulletin board display media-assisted recitation method